2009
DOI: 10.1080/01932690902766319
|View full text |Cite
|
Sign up to set email alerts
|

Letter: The IEP of Carbonate-Free Neodymium(III) Oxide

Abstract: INTRODUCTIONSeveral metal oxides spontaneously react with atmospheric CO 2 to produce metal carbonates. The particles of these oxides, which have been exposed to atmospheric CO 2 are covered with carbonate layers. A relatively low mass fraction of carbonate may substantially change the surface properties of an oxide particle if it constitutes the external layer of that particle, which is the case for originally carbonate-free metal oxide exposed to atmospheric CO 2 . The presence of carbonate induces a shift i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Furthermore, the lower IEP of TiO 2 nanoparticles can be attributed to the presence of carbonates on the surface of TiO 2 nanoparticles, as can be evidenced by the carbon signal in the EDX results ( Figure 4 ). Kosmulski et al [ 96 ] concluded that the presence of carbonate shifts the IEP of metal oxides to a lower pH. The obtained composites show the highest stability at pH 11 and 12, as for these pH values, each biomaterial has a zeta potential lower than −30 mV, which is the limiting potential for the stability of suspensions [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the lower IEP of TiO 2 nanoparticles can be attributed to the presence of carbonates on the surface of TiO 2 nanoparticles, as can be evidenced by the carbon signal in the EDX results ( Figure 4 ). Kosmulski et al [ 96 ] concluded that the presence of carbonate shifts the IEP of metal oxides to a lower pH. The obtained composites show the highest stability at pH 11 and 12, as for these pH values, each biomaterial has a zeta potential lower than −30 mV, which is the limiting potential for the stability of suspensions [ 97 ].…”
Section: Resultsmentioning
confidence: 99%